Interactive storytelling fourth International Conference on Interactive Digital Storytelling, ICIDS 2011, Vancouver, Canada, November 28-1 December, 2011, proceedings - Si, Mei; Thue, David; Andre, Elisabeth; Lester, James C.; Tanembaum, Joshua; Zammitto, Veronica (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 4th International Conference on Interactive Digital Storytelling, ICIDS 2011, held in Vancouver, Canada, in November/December 2011. The 17 full papers, 14 short papers and 16 poster papers were carefully reviewed and selected from 72 paper and poster submissions. In addition, the volume includes 6 workshops descriptions. The full and short papers have been organized into the following topical sections: interactive storytelling theory, new authoring modes, virtual characters and agents, story generation and drama managment, narratives in digital games, evaluation and user experience reports, tools for interactive storytelling.